Case Report: Fanconi-Bickel Syndrome in a Chinese Girl With Diabetes and Severe Hypokalemia - Chen, Hongbo; Lyu, Juan-juan; Huang, Zhuo; Sun, Xiao-mei; Liu, Ying; Yuan, Chuan-jie; Ye, Li; Yu, Dan; Wu, Jin (Frontiers in Pediatrics, 2022)
Fanconi-Bickel syndrome (FBS) is a rare autosomal recessive carbohydrate metabolism disorder. The main symptoms of FBS are hepatomegaly, nephropathy, postprandial hyperglycemia, fasting hypoglycemia and growth retardation. Hypokalemia is a rare clinical feature in FBS patients. In this study, we present a neonate suffering from FBS. She presented with hypokalemia, dysglycaemia, glycosuria, hepatomegaly, abnormality of liver function and brain MRI. Trio whole-exome sequencing (WES) and Sanger sequencing were performed to identify the causal gene variants. A compound heterozygous mutation (NM_000340.2; p. Trp420*) of SLC2A2 was identified. Here, we report a FBS patient in a consanguineous family with diabetes and severe hypokalemia and other typical FBS symptoms. Patients with common clinical features may be difficult to diagnose just by phenotypes in early stage of life, but WES could be an important tool. We also discuss use of insulin in FBS patients and highlight the importance of continuous glucose monitoring system (CGMS) not only in diagnosis but also to avoid hypoglycemic events.